Evidence-based clinical practice guideline for the treatment of depression in adults at a specialized mental health hospital. Lima, Peru - Vargas Cajahuanca, Gisella (2019)
Introduction. Depression is a mental disorder that in its most severe form can end in suicide. Objective. This Evidence-based Clinical Practice Guideline (EB-CPG) provides recommendations for the pharmacological and psychotherapeutic treatment of depression in adults. Methods. An adapted EB-CPG was elaborated through a systematic, rigorous and transparent process with a team of methodologists and psychiatrists experts in clinical management of the disease. The guide has seven clinical questions and 10 recommendations, the search and preselection of CPGs was carried out responding to the scope and objectives, which were evaluated through the “Appraisal of Guidelines for Research and Evaluation II” (AGREE-II), and the guide with the best methodological quality was selected for methodological adaptation. A systematic search for evidence to answer the clinical questions was made in multiple databases: MEDLINE / PubMed, EMBASE / Ovid, Cochrane Library, LILACS and SciELO. The evidences were selected and critically analyzed by clinical and methodological pairs, the recommendations were elaborated through the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. Results. With the participation of a panel of clinical experts from different reference hospitals in the clinical management of depression, 10 recommendations about the beginning of pharmacological and psychotherapeutic treatment, combined therapy, individual-group psychotherapy, and adverse drug-therapy events were approved for adult patients with depression. Conclusions. This article is a summary of the evidence-based clinical practice guidelines for the treatment of depression in adults in a Peruvian mental health public hospital.